Critical thermodynamics of two-dimensional N-vector cubic model in the five-loop approximation - Calabrese, P.; Orlov, E.V.; Pakhnin, D.V.; Sokolov, A.I. (Condensed Matter Physics, 2005)
The critical behavior of the two-dimensional N-vector cubic model is studied
within the field-theoretical renormalization-group (RG) approach. The
β functions and critical exponents are calculated in the five-loop approximation,
RG series obtained are resummed using Pade-Borel-Leroy and ´
conformal mapping techniques. It is found that for N = 2 the continuous
line of fixed points is well reproduced by the resummed RG series and an
account for the five-loop terms makes the lines of zeros of both β functions
closer to each other. For N > 3 the five-loop contributions are shown to
shift the cubic fixed point, given by the four-loop approximation, towards
the Ising fixed point. This confirms the idea that the existence of the cubic
fixed point in two dimensions under N >2 is an artifact of the perturbative
analysis. In the case N = 0 the results obtained are compatible with the
conclusion that the impure critical behavior is controlled by the Ising fixed
point. В рамках теоретико-польового підходу ренормалізаційної групи (РГ)
вивчається критична поведінка двовимірної N-векторної кубічної
моделі. β функції і критичні показники обчислюються в п’ятипетлевому наближенні, отримані РГ ряди пересумовуються з використанням техніки Паде-Бореля-Лєруа і конформного перетворення.
Знайдено, що для N = 2 неперервна лінія нерухомих точок добре
відтворюється пересумованими РГ рядами і врахування п’ятипетлевих членів робить лінії нулів обох β функцій ближчими один
до одного. Показано, що для N > 3 п’яти-петлеві внески зсувають
кубічну нерухому точку, отриману в чотири-петлевому наближенні,
до нерухомої точки Ізинґа. Це підтверджує ідею, що існування
кубічної нерухомої точки в двох вимірах під N > 2 є результатом
пертурбативного аналізу. У випадку N = 0 отримані результати є
сумісні з висновком, що критична поведінка, пов’язана з домішками,
контролюється нерухомою точкою Ізинґа.